An Investigation into the Factors affecting the adoption of e-Learning in Public Secondary Schools in Makadara district, Nairobi County, Kenya - Mulwa, David Musyoki; Kalui, Fredrick Mukoma; Nyambeki, Makori, Linet (Journal for Humanity Science and English Language, 2014)
The main purpose of the study was to investigate the factors affecting adoption of e-learning in public secondary schools in Makadara District, Nairobi County. The specific objectives of the study were to establish the influence of ICT infrastructure and e-learning curricula and design on the adoption of e-learning in public schools in Makadara district, Nairobi County. It was also aimed at examining the effect of teacher’s readiness and teachers’ ICT skills on the adoption of e-learning in public schools in Makadara District, Nairobi County. The study adopted a survey research design. The study targeted all the head teachers, deputy head teachers and teachers of all public secondary schools in Makadara District. The target population was 195 and a sample of 98 was sampled for the study. Data was collected using a questionnaire. Descriptive and inferential statistical tools were used to analyze the study variables of ICT infrastructure, curricula, teacher readiness, teacher ICT skills and adoption of e-learning. The study established that most schools had low investment in ICT infrastructure due high costs of computer hardware, software and related accessories. The adoption of e-learning implementations has resulted in the need for development of new skills and competencies among teachers as most teachers who have been teaching in traditional manners are not technologically literate and sometimes may even resist because of the worry about losing their jobs if e-learning is implemented, because of their inadequate skills. The factors affecting the adoption of e-learning significantly influenced the adoption of e-learning and external factors such as the government policies, financial policies and human development. The study recommends that there is need for schools to have e-learning infrastructure included in the financial plans to cater for maintenance and expansion of the ICT infrastructure and the acquisition and maintenance and training of teachers and technical staff, e-learning curricula may need to be designed in such a way that is relevant in the quality of information with the outside world because students will use different resources besides their instructor, teachers need to acquire necessary knowledge and skills that allows them to shift from traditional teaching experiences to an e-learning teaching style hence school official need to avail adequate technical support at the beginning of the adoption of elearning program.
Keywords: E-learning; Secondary schools